PENGARUH GERAKAN WANITA TERHADAP WACANA HUKUM ISLAM: Studi Hukum Perkawinan Indonesia - Nasution, Khoiruddin (Al-Mawarid Jurnal Hukum Islam, 2005)
The paper discusses role and influence of women movement in formulating the Marriage Law of Indonesian no. 1 of 1974. The issue described by citing the historical fact since the coming out of the issue of the important of marriage law to replace traditional Islamic marriage (fiqh), process of the emergence until promulgation and the result of the law. By so doing hopefully it will be able to understand the role and the influence of Indonesian women movement in formulating and contend of the law. What is found therefore is that women movement played an important role and influenced contend of the law. To prove this conclusion is first of all that women are the first group proposed of the important of promulgation of marriage law both individually and collectively (organization). Secondly, one of the objectives of the promulgation of marriage law is to improve the status of women. The third, majority of the content of marriage law is put women more equal with men. Key words: Indonesia, influence, Islamic marriage law, women movement.